Does Student Work Really Affect Educational Outcomes? A Review of the Literature - Brecht Neyt; Eddy Omey; Dieter Verhaest; Stijn Baert (Global Labor Organization (GLO), 2017)
We review the theories put forward, methodological approaches used, and empirical conclusions found in the multidisciplinary literature on the relationship between student employment and educational outcomes. A systematic comparison of the empirical work yields new insights that go beyond the overall reported negative effect of more intensive working schemes and that are of high academic and policy relevance. One such insight uncovered by our review is that student employment seems to have a more adverse effect on educational choices and behaviour (study engagement and the decision to continue studying) than on educational performance (in particular, graduation).
Keywords: I21; J22; J24; 330; student employment; education; self-selection; review